Slovene independence never happened, or how to reconstruct the historical mode of politics? - Kirn, Gal (Monitor ISH, 2007)
The main task of the article is to analyze two ruptures that suspended time and produced space. The article engages in the critical dialogue with the dominant conception of time and space via historical reconstruction of recent Slovene history. If in the 1980s the amalgam of politics (new social movements), art and theory appeared in and broke up with the dominant situation, the 1990s saw the occupation of Metelkova, which evolved into one of the biggest autonomous centres in Europe. With the help of Alain Badiou's theory, the author reaches the conclusion that the independence of Slovenia never took place.
Keywords: Slovenia; Slovenija; Confederation of New Trade Unions of Slovenia "Independence"; neodvisnost; prostor in čas; dogodek; Metelkova; družbena gibanja; slovenska zgodovina